Improving Radioactivity Learning Outcomes With Recreational Charta Media - Murtiatmi Warnaningtyas (Universitas Muhammadiyah Enrekang, 2023)
The purpose of this study was to improve the learning outcomes of radioactivity in X TBO 3 students using recreational chart media for the 2021/2022 school year, with a total of 35 students. The research used was Classroom Action Research (CAR), which was carried out in two cycles. Each cycle consists of the stages of planning, implementing, observing and reflecting. The data collection technique used is the direct method, namely from the test results in each cycle. Based on the results and discussion, it was obtained that the average value in cycle I was 71 and in cycle II it was 74, so that it can be seen that there was an increase in the average value from cycle I to cycle II. So it can be concluded that using chart media can improve the learning outcomes of class X TBO 3 radioactivity students.